Addiction stigma and the biopolitics of liberal modernity: A qualitative analysis - Fraser, Suzanne; Pienaar, Kiran; Dilkes-Frayne, E.; Moore, David; Kokanovic, R.; Treloar, C.; Dunlop, A. (Elsevier BV, 2017)
Definitions of addiction have never been more hotly contested. The advance of neuroscientific accounts has not only placed into public awareness a highly controversial explanatory approach, it has also shed new light on the absence of agreement among the many experts who contest it. Proponents argue that calling addiction a 'brain disease' is important because it is destigmatising. Many critics of the neuroscientific approach also agree on this point. Considered from the point of view of the sociology of health and illness, the idea that labelling something a disease will alleviate stigma is a surprising one. Disease, as demonstrated in that field of research, is routinely stigmatised. In this article we take up the issue of stigma as it plays out in relation to addiction, seeking to clarify and challenge the claims made about the progress associated with disease models. To do so, we draw on Erving Goffman's classic work on stigma, reconsidering it in light of more recent, process oriented, theoretical resources, and posing stigmatisation as a performative biopolitical process. Analysing recently collected interviews conducted with 60 people in Australia who consider themselves to have an alcohol or other drug addiction, dependence or habit, we explore their accounts of stigma, finding experiences of stigma to be common, multiple and strikingly diverse. We argue that by treating stigma as politically productive - as a contingent biopolitically performative process rather than as a stable marker of some kind of anterior difference - we can better understand what it achieves. This allows us to consider not simply how the 'disease' of addiction can be destigmatised, or even whether the 'diseasing' of addiction is itself stigmatising (although this would seem a key question), but whether the very problematisation of 'addiction' in the first place constitutes a stigma process.